UTILIZATION OF DIGITAL TECHNOLOGY IN THE LEARNING PROCESS OF STUDENTS AT AL-AZHAR PRIVATE HIGH SCHOOL MEDAN - Ahmad Hafidz Minal Abrar; Syifa Izzati Khalilah Zaman; Nailah Khairiyah Assalih Harahap; Rava Akbar Harahap; Fathul Ghifari Pinem (PT. Radja Intercontinental Publishing, 2025)
The use of digital technology in education has had a significant impact on students' learning processes. This article aims to examine the extent to which digital technology plays a role in improving the quality of learning, expanding access to information, and creating more interactive learning patterns. This research uses a literature review method by reviewing various relevant literature related to the use of digital technology in education. The results of the study indicate that digital technology can increase learning motivation, facilitate collaboration, and support 21st-century skills such as critical and creative thinking. However, there are also challenges faced, including the digital divide, lack of digital literacy among students, and limited infrastructure. Therefore, an active role is needed for teachers, schools, and the government in optimizing the use of digital technology to make the learning process more effective, equitable, and sustainable.